1999
DOI: 10.1007/s11746-999-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of peroxide value in thermally oxidized crude palm oil by near infrared spectroscopy

Abstract: A near infrared (NIR) spectroscopic method was developed to measure peroxide value (PV) in crude palm oil (CPO). Calibration standards were prepared by oxidizing CPO in a fermentor at 90°C. A partial least squares (PLS) calibration model for predicting PV was developed based on the NIR spectral region from 1350 to 1480 nm with reference to single-point baseline at 1514 nm. The optimization of calibration factors was guided by the predicted residual error sum of squares test. The standard error of calibration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 8 publications
(10 reference statements)
1
24
1
Order By: Relevance
“…Among the unsaturated fatty acids oleic acid C18:1 n9 was found to be main fatty acid ranged between 33.54-44.05 . Oleic acid C18:1 n9 in present PFAD samples was found higher than earlier reports 17,18 . Table 3 represents the important groups and ratios of fatty acids in PFAD.…”
Section: Fatty Acid Compositioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Among the unsaturated fatty acids oleic acid C18:1 n9 was found to be main fatty acid ranged between 33.54-44.05 . Oleic acid C18:1 n9 in present PFAD samples was found higher than earlier reports 17,18 . Table 3 represents the important groups and ratios of fatty acids in PFAD.…”
Section: Fatty Acid Compositioncontrasting
confidence: 80%
“…In this study, IV was found in the range of 38.49-63.10 g I 2 /100 g with mean value of 51.24 g I 2 /100 g. IV found in this study was lower than reported studies 17,20 . 18 . SV of PFAD samples is important parameter which is often applied in soap and cosmetic industries 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The following conclusions would be drawn from Table 1: (a) for all parameters and for both oils, FFA, TPC, and VIS were increased upon heating and this was expected due to hydrolysis, oxidation, and polymerization of vegetable oils at higher frying temperatures, (b) it seems that PO has more resistance to oxidation compare to SO and this is reported in literature (Moh et al 1999). As indicated in Table 1 intrinsic ability of the oil for resisting frying conditions.…”
Section: Assessment Of Frying Oilssupporting
confidence: 62%
“…Therefore, spectroscopic methods are being increasingly used to replace wet chemical procedures. Infrared spectroscopy is one that has found increased use due to its low cost, shorter analysis time, non-destructiveness and small sample quantities, in addition to accuracy and reliability when associated with chemometric methods [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%